Qual o resultado de (X + 4 , y - 1) = (-3,6)
Soluções para a tarefa
Respondido por
1
Resolução:
(x + 4 , y - 1) = (- 3 , 6)
x + 4 = -3 y - 1 = 6
x = - 3 - 4 y = 6 + 1
x = -7 y = 7
bons estudos:
(x + 4 , y - 1) = (- 3 , 6)
x + 4 = -3 y - 1 = 6
x = - 3 - 4 y = 6 + 1
x = -7 y = 7
bons estudos:
Respondido por
1
Olá, bom dia ☺
Resolução:
(x + 4 , y - 1) = (-3,6)
----------------------------------
x + 4 = - 3.
x = - 3 - 4
x= - 7
----------------------------------
y - 1 = 6
y = 6 + 1
y = 7
Bons estudos :)
Resolução:
(x + 4 , y - 1) = (-3,6)
----------------------------------
x + 4 = - 3.
x = - 3 - 4
x= - 7
----------------------------------
y - 1 = 6
y = 6 + 1
y = 7
Bons estudos :)
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás